Factors Inhibiting the Implementation of Electronic Medical Records in the Inpatient Department of Hospital X in Bandung - Suryani, Ade Irma; Apriyani, Puput (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
The development of the internet in the healthcare sector, particularly in the implementation of electronic medical records (EMR), aims to enhance the effectiveness of inpatient services at Hospital X in Bandung. The study employed a qualitative descriptive method, with data collected through field observations, literature reviews, and interviews with the head of the medical records department and six medical record staff members. The research findings indicate that the implementation of EMR at the hospital has been progressing well. However, some challenges were identified, such as the inefficiency of three registration staff members due to frequent computer or network (LAN) issues. Additionally, the transition to EMR has taken longer because the staff are still adjusting to the new system. As a solution, the study recommends regular maintenance of the infrastructure supporting EMR and continuous socialization and training programs for staff. These suggestions are expected to improve the effectiveness of EMR utilization at the hospital.